PLEDOI PAULUS ATAS KERASULANNYA - Edi Rundjan; Hikman Sirait; Finky Kantohe (The Way Jurnal Teologi dan Kependidikan, 2019)
Some of the purposes of writing this research are to understand Paul's intentions in Galatians 1 and 2 of his Apostolic Pleidio; To find answers to problems and questions about Paul and his Apostleship. Because this question has major implications for understanding the Bible and also today's life; So that God's servants can make this research as a reference to understand the importance of accountability for the service of each person, so that the call can be more interpreted. The research method used is a qualitative method with a synchronous approach and uses library study (library research). A clear basis of service will lead to more effective service, it is also acceptable not to bring those served in the wrong direction. Apostles Called, Chosen and Sent directly by Jesus. The researcher found that, Paul's first defense of his apostolic validity was the basis of his calling, election and sending which he received directly from Jesus Christ. In the same section regarding the discussion of Galatians 1:13-24, Paul's apostolate not only theoretically he said was something he received directly from Jesus Christ, but he also testified of his personal encounter with Jesus was the starting point for Paul's conversion and the beginning of the apostolate is given. Paul fulfills the same apostolic criteria as the other apostles. The research tries to give an understanding of the importance of the responsibility of every servant of God for the call of service received and do in the life of a servant of the Lord by turning to Paul who is responsible for his legal call to questions that are doubtful his apostolate.